Guru Pembimbing Khusus (GPK) di Sekolah Inklusi Palangka Raya: Shadow Teacher of Inclusive School in Palangka Raya - Gerry Olvina Faz; Istiqamah Hafid (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Inclusive schools provide opportunities for Children with Special Needs/ Anak Berkebutuhan Khusus (ABK) to study in public schools, and Shadow Teacher/ Guru Pembimbing Khusus (GPK) are an important part of implementing this inclusive school program. This research was conducted to analyze the role and implementation of GPK in Palangka Raya. The results of this study able to applied in inclusive school system and optimize GPK in carrying out their duties in class. The research methodology used is qualitative research and data analysis uses thematic analysis with an inductive approach. The results of this study are, first the role of GPK includes the learning process and encourages social acceptance in the classroom. Second, the pattern of interaction between GPK, schools, and parents influences the optimization of ABK learning at school. Third, GPK has emotional attachment and empathy towards ABK and parents. The conclusion of this study is that there is no standardized procedure for GPK to carry out their duties, but in general GPK is able to do their tasks with the support of their resources. In addition, the pattern of interaction between GPK, parents and schools basically influence the implementation of inclusive education in schools.